1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

Solve the following pair of equation 5xâˆ’1 + 1yâˆ’2 = 2 6xâˆ’1 - 3yâˆ’2 = 1

A

4,5

Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
B

5,3

No worries! Weâ€˜ve got your back. Try BYJUâ€˜S free classes today!
C

1/3, 1/3

No worries! Weâ€˜ve got your back. Try BYJUâ€˜S free classes today!
D

None of these

No worries! Weâ€˜ve got your back. Try BYJUâ€˜S free classes today!
Open in App
Solution

The correct option is A 4,5 If we substitute 1x−1 as p and 1y−2as q in the given equations. We get the equations as 5p+q=2 6q-3q=1 Now we can solve the pair of equation by method of elimination. 15p+3q=6 6p-3q=1 Adding both p= 13 Now by substituting the value in one of the equation we find q= 13 AS we have assumed p = 1x−1 Therefore, 1x−1 = 13 → x = 4 Similarly we assumed q = 1y−2 1y−2 = 13 → y - 2 = 3 → y = 5 Thus x=4, y=5

Suggest Corrections
30
Join BYJU'S Learning Program
Related Videos
Solving Linear Equations
MATHEMATICS
Watch in App
Join BYJU'S Learning Program